LANGUAGE SERIAL VERB CONSTRUCTION DAYAK KENYAH LEPO’ TAU - Ahmad Dicky Romadhan (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study discusses the construction of serial verbs in the Lepo Dayak Kenyah language 'Tau.This research is a qualitative descriptive type. The data in this study were taken from nativeLepo Dayak Kenyah speakers. The collection technique uses the listening technique and notesaccompanied by elicitation techniques. The results of this study state that the construction ofserial verbs in the Lepo 'Tau Dayak Kenyah language has the same characteristics as theextensive serial verb construction typology. In this study also found several semantic types inthe construction of serial verbs in the Lepo 'Tau Dayak Kenya language, namely type ofmovement, directional type, type of type, cause-effect type, type of modality and type of aspect.